2,6-Diamino-4-oxo-3,4-dihydropyrimidin-1-ium chloride dihydrate - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
In the crystal structure of the title compound, C(4)H(7)N(4)O(+)center dot-Cl-center dot 2H(2)O, adjacent cations are connected to one another through N-H center dot center dot center dot O hydrogen bonds, forming infinite chains along the b axis. These chains are further hydrogen bonded to the chloride anions and water molecules, resulting in a three-dimensional network. The pyrimidine rings of adjacent molecules are arranged in an antiparallel manner above each other with centroid-centroid distances of 3.435 (1) angstrom, indicative of pi-pi interactions.